Integrated Legal Education on the Dangers of Drugs and Their Prevention for Students of IT IT Middle School Insan Mulia, Sungai Intan Village, Tembilahan Hulu District, Indragiri Hilir Regency - Fitri Wahyuni; Syarifuddin Syarifuddin; Siti Rahmah; Darmiwati Darmiwati; Muhsin Muhsin; Wandi Wandi (KARYA ABDI, 2020)
The misuse and circulation of illicit drugs is a widespread, complex, and complex issue facing the Indonesian people lately, as it can have many negative effects, especially among the younger generation. Therefore, massive prevention efforts must be made through integrated legal counsel such as the Faculty of Law of the Islamic University of Islamic Universities in schools. One of the selected schools is the Junior High IT IT High School located in the Sungai Intan Village of West Suburban Suburban Suburban Hulu district. In the implementation of the counseling the aim is for students to understand the dangers of drugs and to avoid the dangers of drugs so that they can become better generations and work better. This method of implementing community service activities is done with data collection techniques through Library and lecture studies. The source of data obtained in the practice of public service counseling is secondary data consisting of: primary legal materials, and secondary legal materials. While analyzing data using a deductive thinking method, it is a mindset based on common things and then draws on specific conclusions. Results and discussion. Commitment activities to the community of legal counsel on Drug Danger and its Prevention for Students / Junior High School IT High School People in Sungai Intan Suburban Suburban District Upstream from the stages of activity preparation, implementation and closure. At the time of implementation each drug dealer presented the drug and its preventive material. The activity received excellent response from the participants as evidenced by the many questions from the participants and the increased knowledge of the participants about the dangers of drugs and their prevention